EFEKTIVITAS MODEL ENVIROMENTAL LEARNING BERBASIS EKSPERIMEN TERHADAP HASIL BELAJAR SISWA KELAS XI SMAN 3 BULUKUMBA - Ismail Syukri; Muh Syihab Ikbal; Hamsiah Djafar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students at SMAN Bulukumba, due to learning still being conventional, which only causes students to lose interest in the learning process. This research aims to: (1) find out the learning outcomes of students taught using the Experiment-Based Environmental Learning model in class XI of SMAN 3 Bulukumba; (2) find out the learning outcomes of students taught using conventional learning in class XI of SMAN 3 Bulukumba; (3) find out the differences in learning outcomes of students taught using the Experiment-Based Environmental Learning model and the conventional learning model in class XI of SMAN 3 Bulukumba. This study uses a quasi-experimental approach with the Matching Only Posttest Control Group Design. The samples used were classes XI-7 and XI-3. The research data were analyzed using descriptive analysis and inferential statistical analysis. The results of the study showed that the learning outcomes of students taught using experiment-based Environmental Learning in class XI at SMAN 3 Bulukumba were in the high category. Meanwhile, the learning outcomes of students taught conventionally were in the sufficient category. The difference between the Environmental Learning model and the conventional learning model can be seen from the average learning outcomes of both. The Environmental Learning model is more effective to use in the learning process than conventional learning. Therefore, it can be concluded that research using the Environmental Learning model can improve students' learning outcomes